Sequential Hybrid Procedure for Persistent Atrial Fibrillation. Issue 3 (25th March 2015) - Bulava, Alan; Mokracek, Ales; Hanis, Jiri; Kurfirst, Vojtech; Eisenberger, Martin; Pesl, Ladislav
Abstract : Background: Catheter ablation of persistent atrial fibrillation yields an unsatisfactorily high number of failures. The hybrid approach has recently emerged as a technique that overcomes the limitations of both surgical and catheter procedures alone. Methods and Results: We investigated the sequential (staged) hybrid method, which consists of a surgical thoracoscopic radiofrequency ablation procedure followed by radiofrequency catheter ablation 6 to 8 weeks later using the CARTO 3 mapping system. Fifty consecutive patients (mean age 62±7 years, 32 males) with long‐standing persistent atrial fibrillation (41±34 months) and a dilated left atrium (>45 mm) were included and prospectively followed in an unblinded registry. During the electrophysiological part of the study, all 4 pulmonary veins were found to be isolated in 36 (72%) patients and a complete box‐lesion was confirmed in 14 (28%) patients. All gaps were successfully re‐ablated. Twelve months after the completed hybrid ablation, 47 patients (94%) were in normal sinus rhythm (4 patients with paroxysmal atrial fibrillation required propafenone and 1 patient underwent a redo catheter procedure). The majority of arrhythmias recurred during the first 3 months. Beyond 12 months, there were no arrhythmia recurrences detected. The surgical part of the procedure was complicated by 7 (13.7%) major complications, while no serious adverse events were recorded during the radiofrequency catheter part of the procedure. Conclusions: The staged hybrid epicardial–endocardial treatment of long‐standing persistent atrial fibrillation seems to be extremely effective in maintenance of normal sinus rhythm compared to radiofrequency catheter or surgical ablation alone. Epicardial ablation alone cannot guarantee durable transmural lesions. Clinical Trial Registration: URL:www.ablace.cz Unique identifier: cz‐060520121617